Răspunsuri

  • Utilizator Brainly
2014-11-12T15:01:27+02:00
1.a)(3 \sqrt{2}+1)(3 \sqrt{2}-1)=  (3 \sqrt{2})^2-1^2 =9*2-1=17 \\ 
b)( 5+\sqrt{3})( 5- \sqrt{3})=5^2-( \sqrt{3})^2=25-3=22 \\ 
c)(2 \sqrt{2}+3)(2 \sqrt{2}-3)  =(2 \sqrt{2})^2-3^2= 8-9=-1 \\  \\ 
2.a)(x+2y)(x-2y)=x^2-(2y)^2=x^2-4y^2 \\ 
b)( \sqrt{2}a-b)( \sqrt{2}a+b)=( \sqrt{2}a)^2-b^2=2a^2-b^2 \\ 
c)(3b-c)(3b+c)=(3b)^2-c^2=9b^2-b^2
1.a)(3 \sqrt{2}+1)(3 \sqrt{2}-1)= (3 \sqrt{2})^2-1^2 =9*2-1=17 \\ 
b)( 5+\sqrt{3})( 5- \sqrt{3})=5^2-( \sqrt{3})^2=25-3=22 \\ 
c)(2 \sqrt{2}+3)(2 \sqrt{2}-3) =(2 \sqrt{2})^2-3^2= 8-9=-1 \\ \\ 
2.a)(x+2y)(x-2y)=x^2-(2y)^2=x^2-4y^2 \\ 
b)( \sqrt{2}a-b)( \sqrt{2}a+b)=( \sqrt{2}a)^2-b^2=2a^2-b^2 \\ 
c)(3b-c)(3b+c)=(3b)^2-c^2=9b^2-b^2